Synthesis of Composite Nanosheets of Graphene and Boron Nitride and Their Lubrication Application in Oil. Issue 2 (29th September 2017) - Liu, Yuchen; Mateti, Srikanth; Li, Chao; Liu, Xuequan; Glushenkov, Alexey M.; Liu, Dan; Li, Lu Hua; Fabijanic, Daniel; Chen, Ying
Abstract : Composite nanosheets of graphene and boron nitride have been produced in large quantities for the first time using high‐energy ball milling in ammonia gas as an exfoliation agent. The anti‐wear properties of the composite nanosheets as a lubricant additive are investigated via a four‐ball method. The results show that the composite nanosheets are exfoliated from the commercial graphite and h‐BN powders and combined into graphene/BN composite nanosheets during the ball milling process. The composite nanosheets formed have diameters larger than 200 nm and consist of heterostructures of approximately 10 monolayers of graphene and BN. The composite nanosheets exhibit better wear resistance and friction reduction properties than the homogeneous nanosheets because of the stronger interaction between graphene and BN nanosheets, which can effectively improve the anti‐wear properties of mineral base oil as a lubricant additive. Abstract : The graphene/BN composite nanosheets produced by gas‐assisted ball milling process form a protection film on the testing material surface leading to a lower friction coefficient and improved anti‐wear properties.